Irisin may change the monoamine levels in different regions related to the sexual behavior of the male rat brain - Ertugrul, N. U.; Yardimci, A.; Ozdede, M. R.; Ozgen, A.; Ozbeg, G.; Canpolat, S. (Wiley, 2022)
[Abstract Not Available]
Keywords: Exercise